-6f3f=-72

Simple and best practice solution for -6f3f=-72 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6f3f=-72 equation:



-6f^3f=-72
We move all terms to the left:
-6f^3f-(-72)=0
We do not support efpression: f^3f

See similar equations:

| 7(n−83)=91 | | -1=1/4(-m-19) | | 3(5+x)=9+9 | | 3=4.9(x^2) | | 2x^2+1=-39 | | e+e=48 | | -3+-2v=7 | | 36=11-(2z-6) | | 1/4x1/3=71/6 | | 2x+x+(x+10)+(2x-16)=360 | | -7f=56-f | | X^2+5x-7=x+5 | | d-12d=77 | | 14n=35,n= | | -(4x-3)=-7(9+x) | | 110+x+44+x+35=180 | | 4c-6c=18 | | 11-5×x=1 | | -7(3x+4)=35 | | 49=7r,r | | V=(200-2x)(150-2x) | | l5-8|-2|=75 | | 9b-6b=39 | | 5x+1+6x=-120 | | 4/5=h/16 | | 34=16-(2z-7) | | 49=7rr | | 2m+6=3-4m | | m(m2-5m+2)=-8 | | 60+70+x+62=180 | | 2.5x+7.75=19 | | 7(6m-8)=112 |

Equations solver categories